Evolution of localized surface plasmon resonance made of gold nanowire chain embedded in WS2 multilayers. (2021) - Oumekloul, Z.; Achaoui, Y.; Mir, A.; Akjouj, A.
Abstract: Recently, the transition metal dichalcogenides (TMDs) have emerged as a new class of building blocks for engineering enhanced plasmonic sensors. This class of materials can be made with a low production cost and can be easily hybridized with metallic nanoparticles whereby desired molecules are thoroughly detected. In this work, we evidence coupling between metallic gold nanowires and a WS2 multi-layer. The novelty lies in the resilient stability of the effect of the thickness layer variation on both, the sensitivity performances and the electric field distribution in the visible and near-infrared spectra. Such configuration can consequently be regarded as an unwavering avenue towards conception of promising and reliable new generation of sensors.